2011
DOI: 10.1111/j.1476-5381.2011.01508.x
|View full text |Cite
|
Sign up to set email alerts
|

Amelioration of central cardiovascular regulatory dysfunction by tropomyocin receptor kinase B in a mevinphos intoxication model of brain stem death

Abstract: BACKGROUND AND PURPOSE Little information exists on the mechanisms that precipitate brain stem death, the legal definition of death in many developed countries. We investigated the role of tropomyocin receptor kinase B (TrkB) and its downstream signalling pathways in the rostral ventrolateral medulla (RVLM) during experimental brain stem death. EXPERIMENTAL APPROACH An experimental model of brain stem death that employed microinjection of the organophosphate insecticide mevinphos bilaterally into the RVLM of S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 54 publications
0
10
0
Order By: Relevance
“…It was administered intravenously, with saline serving as the vehicle control. Temporal changes in pulsatile AP, mean AP (MAP), HR and power density of the LF component were routinely followed for 20 min in an on-line and real-time manner [14] , [16] , [52] , or until the animal succumbed to METH. The survival rate within 240 min was also recorded.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It was administered intravenously, with saline serving as the vehicle control. Temporal changes in pulsatile AP, mean AP (MAP), HR and power density of the LF component were routinely followed for 20 min in an on-line and real-time manner [14] , [16] , [52] , or until the animal succumbed to METH. The survival rate within 240 min was also recorded.…”
Section: Methodsmentioning
confidence: 99%
“…Simultaneous and continuous measurement of tissue oxygen tension, blood flow and temperature (Oxford Optronix, Oxford, England) was carried out by a combined oxygen/temperature/blood flow probe stereotaxically positioned into the RVLM [14] , [52] . The coordinates used were: 4.5 to 5 mm posterior to lambda, 1.8 to 2.1 mm lateral to midline and 8.1 to 8.4 mm below dorsal surface of cerebellum.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, the phosphorylation of ATF-2 in Thr71 and of c-Jun in Ser73 in RVLM was also increased during this phase Chan et al [48]. Furthermore, Chan et al [49] have shown that Mev induced pro-life brainstem death via NO produced by NOS I in the Rostral Ventrolateral Medulla (RVLM), followed by stimulation of the soluble guanylyl cyclase/cGMP/PKG cascade. Further, it was shown that Bis (pinacolylmethyl) phosphonate (BPMP) induced the ERK signaling pathway to cause vacuolation in mitochondria in cultured rat astrocytes, and the authors suspected that the activated Ras/Raf-1/ERK signaling pathway was involved in modulating central cardiovascular function through NOS I/PKG upregulation [50].…”
Section: Organophosphorus Compound-induced Neurodegenerative Diseasesmentioning
confidence: 96%
“…More importantly, the distinct phases of augmentation followed by reduction of the LF power exhibited during Mev intoxication [14-17] can be designated the pro-life and pro-death phase of central cardiovascular regulation in this model of brain stem death [6]. Based on this model, our laboratory has previously demonstrated that activation of MAPK kinase 1/2 (MEK1/2) in RVLM, followed by ERK1/2 and MAPK signal-interacting kinase 1/2 (MNK1/2) activation, is responsible for the pro-life phase by sustaining the central cardiovascular regulatory machinery during brain stem death [18,19]. …”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, we previously demonstrated that ERK1/2 in RVLM plays a pro-life role in experimental brain stem death [18,19]. In our continual search for the cellular and molecular underpinning of brain stem death, the next logical direction is to evaluate the contribution of the other two family members of MAPKs, JNK or p38MAPK in RVLM to this fatal phenomenon.…”
Section: Introductionmentioning
confidence: 99%